Pengaruh Metode Ekstraksi Terhadap Kadar Flavonoid Total dan Aktivitas Antioksidan Tanaman Kenop (Gomphrena globosa) - Ramadhan, Rohan; Sari, Asti Arum (Journal of Pharmaceutical and Sciences, 2025)
Gomphrena globosa is a medicinal plant with attractive pigments and therapeutic properties, including antihypertensive, anticancer, and antioxidant effects. These activities are mainly attributed to phenolic compounds such as flavonoids. Previous studies have shown that ethanolic extracts of G. globosa flowers and leaves obtained by maceration have potent antioxidant activity. However, no study has yet reported Soxhlet extraction of G. globosa leaves. Therefore, this study aimed to compare Soxhlet extraction and maceration extraction methods to evaluate their efficiency in extracting flavonoids and antioxidant activity. Flavonoid levels were determined using the aluminium chloride colourimetric method with quercetin as a standard, and antioxidant activity was evaluated using the DPPH radical scavenging assay. The results showed that maceration produced a higher flavonoid content (78.33 ± 2.14 mg QE/g extract) than Soxhlet extraction (57.43 ± 1.53 mg QE/g extract). Consistently, antioxidant activity was more potent in the macerated extract (IC₅₀ = 53.93 ± 1.78 μg/mL) compared to the Soxhlet extraction (IC₅₀ = 62.50 ± 0.39 μg/mL). Evaluation using the t-test showed that the antioxidant activities of these methods were significantly different (p < 0.05). These findings indicate that maceration is more effective in extracting flavonoids from G. globosa leaves, resulting in high antioxidant activity. Moreover, G. globosa leaves emerged as a promising natural antioxidant source for pharmaceutical and functional food applications.